Parental Depressive Symptoms and Parenting: Associations with Children’s Coping in Families of Depressed Parents - Henry, Lauren M. (Parent Sci Pract, 2018)
OBJECTIVE. This multi-method study examined parental depressive symptoms and levels of harsh/intrusive and warm/responsive parenting as correlates of secondary control coping (acceptance, cognitive reappraisal, distraction) in children of parents with a history of depression. DESIGN. The sample included 165 parents with a history of major depressive disorder and their 9- to15-year-old children. Parents provided self-reports of their current depressive symptoms; videorecordings of parent-child interactions were coded to determine parenting behaviors; and children reported their use of secondary control coping strategies. RESULTS. Harsh/intrusive parenting related to less, and warm/responsive parenting related to greater, use of secondary control coping strategies in children. Parents’ current depressive symptoms were only conditionally related to children’s use of secondary control coping strategies, such that depressive symptoms moderated the relation between warm/responsive parenting behaviors and child secondary control coping. When parental depressive symptoms were low or average, warm/responsive parenting was positively related to children’s secondary control coping. When parental depressive symptoms were high, warm/responsive parenting was not associated with children’s secondary control coping. CONCLUSIONS. The association between positive parenting behaviors and children’s coping is contingent on current levels of parents’ depressive symptoms. Efforts to enhance children’s coping skills should target both parental depressive symptoms and parenting skills.